2022
DOI: 10.1115/1.4055100
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Yield in Single Slope Solar Still by Composite Heat Storage Material—Experimental and Thermo-Economic Assessment

Abstract: The main objective of this study is to enhance the yield of single slope solar still by extending the operating time of solar still by utilizing composite heat storage materials in the solar still. In this regard, the effect of the composite heat energy storage material developed by the mixture of beach sand with paraffin wax is investigated. The experiments are carried out in Solar Still with Composite Heat Storage Material (SSCHSM), and results are compared with Solar Still with Sensible Heat Storage Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The water and absorber temperatures of solar still with PCM are significantly improved by about 10% using RT-58 under the absorber basin. 7 Solar still with ball marbles 36.67 1.9 5.7 Suraparaju and Natarajan 30 Solar still with PCM and natural fibres 126.90 1.6 3.6 Suraparaju and Natarajan 37 Solar still with hollow fins & PCM 41.67 2.3 6.3 Sampathkumar et al 49 Solar still with composite PCM 64% 2.28 6.2 Modi et al 50 Solar still with nanofluids 58.25 1.5 6.9 Nayi and Modi 51 Pyramid solar still with energy storage 11.35 2.6 11.3…”
Section: Discussionmentioning
confidence: 99%
“…The water and absorber temperatures of solar still with PCM are significantly improved by about 10% using RT-58 under the absorber basin. 7 Solar still with ball marbles 36.67 1.9 5.7 Suraparaju and Natarajan 30 Solar still with PCM and natural fibres 126.90 1.6 3.6 Suraparaju and Natarajan 37 Solar still with hollow fins & PCM 41.67 2.3 6.3 Sampathkumar et al 49 Solar still with composite PCM 64% 2.28 6.2 Modi et al 50 Solar still with nanofluids 58.25 1.5 6.9 Nayi and Modi 51 Pyramid solar still with energy storage 11.35 2.6 11.3…”
Section: Discussionmentioning
confidence: 99%
“…These attributes render it a relevant preference for utilization in machining operations [34]. A limited number of researchers have explored the incorporation of nanoparticles to improve thermal properties [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Sampathkumar et al 28 conducted the impact of a mixture of beach sand with paraffin wax as hybrid storage materials on the yield of solar distillers. They found that the yield improved from 1820 to 2950 mL/m 2 for using hybrid storage materials.…”
Section: Introductionmentioning
confidence: 99%